Determine New Product and Service Development in Health Ecosystems in Malaysia in conjunction with the new crisis - Ali, Hebatallah Mostafa (Technium Social Sciences Journal, 2021)
Healthcare has encountered significant challenges over the past few years in order to modify its policies and strategies to experience the stress of elevating costs, innovation, and altering regulations (Annanperä, Liukkunen & Markkula, 2015). In this regard, new product development is one of the sparkling issues. A massive amount of the research budget is invested to innovation, specifically for innovative or novel biotechnological, pharmaceutical, health and medical services or products (Koskela-Huotari et al., 2016). A new cultural setting is emerging, emphasized on per-requisites, which have to be collaborated with technologies and innovations so as to fulfill successful objectives (Wartena, Muskens & Schmitt, 2009). Consequently, this study has emphasized on the analysis of an innovative service ecosystem that is a private clinic providing services for kidney diseases. Comprehending healthcare as a service ecosystem needs emphasis not merely on a focal firm approach to innovation emerging from an innovative tactic to resource integration or from service innovation, but also on undertaking the limelight of various internal and external stakeholders in the revitalizing of medical services. Therefore, a qualitative analysis based on the interviews from various stakeholders of health ecosystem is conducted.